(untitled) (Scripta : English Department Journal, 2022)
The purpose of this study is to improve students’ vocabulary skills through outdoor learning activity. This research was conducted in SMP Islam Ruhama, Cirendeu. The population of this research was seventh-grade students in academic year 2022/2023. The sample of this research was 7.1 consists of 24 students. The method of this study was quantitative method and using pre-experimental design. To collect the data, the researcher used pre-test and post-test as an instrument that given to the students. The data were analyzed by using the formula statistical computerization repeated measures (paired samples t-test) of SPSS V.28. The result score of the data indicated that the average in pre-test was (51,45). And the total average in post-test were (84,79). There was a significance different from the result post-test score was higher than pre-test score. Thus, it can be concluded that the Outdoor Learning Activity has a significant effect on the vocabulary skills of students in class 7.1 at SMP Islam Ruhama, Cirendeu.